Classification of Obstacles to Enterning into Marriage and the Particularities of Worship of the Sacrament of Marriage in the Orthdox Church - Vakin, Vlodymyr (2018)
Marriage, as a union between a man and a woman, is not only the basis of a social system and a guarantee of the continuation of human race, but most importantly, it has a divine guidance and origin. From the very beginning of the New Testament Church of Christ, there was no conflict between the Church doctrine of marriage and secular law of the Roman Empire. Howeverm after the publication of the Edict of Milan, the Church legal status in the Roman Empire redically changed, and thus a fruitful long-term cooperation in legislation of the marriage law formation of the Orthodox Church began. We can conclude that within this cooperation, the initiative and the dominant idea were absolutely on the side of the Church. Thus, the canons adopted by the ecclesiastical authority, received legislative approval in the legislation novels of the emperors and became obligatory for all inhabitants of the empire. To be fair, it is necessary to note the reciprocal effect of the synergy of this union - many of the state laws have been reflected in church regulations. Therefore, a well-structured and legally sophisticated system of marriage law of the Orthodox Church was formed, which continued ist legal enrichment after the great East-West Schism of 1054 to the present day and has a wide range of local church-state peculiarities of individual Local Churches
Keywords: Georgisch-Orthodoxe Kirche; Eherecht; Ehehindernis